E-Cigarette Advocates on Twitter: Content Analysis of Vaping-Related Tweets - McCausland, Kahlia; Maycock, Bruce; Leaver, Tama; Wolf, Katharina; Freeman, Becky; Jancey, Jonine (JMIR Publications, 2020)
Background: As the majority of Twitter content is publicly available, the platform has become a rich data source for public health surveillance, providing insights into emergent phenomena, such as vaping. Although there is a growing body of literature that has examined the content of vaping-related tweets, less is known about the people who generate and disseminate these messages and the role of e-cigarette advocates in the promotion of these devices.